The financial structure of the Tunisian listed businesses: An application on panel data - Mohamed Soufeljil; Asma Sghaier; Zouhayer Mighri; Hanène Kheireddine (Journal of Global Entrepreneurship Research, 2017)
This article aims at analyzing the financial structure of the Tunisian listed companies in the stock exchange of Tunis (SET). The study focuses on 26 companies observed over a period of 6 years (2005-2010). Three representations of the behavior of funding are tested: The first considers that the firms implement a policy of debt with an objective of debt ratio target, the second presupposes the existence of a hierarchy of funding and divides the existence of a target ratio, the third assumes that firms issuing shares when market conditions are favorable and redeemed in the opposite case. The statistical tests validate better the first approach. In fact, the choice of financing of Tunisian businesses confirms the greatest explanatory power of an analysis based on the existence of a debt ratio target.
Keywords: 650; Tiered funding; Debt ratio target; Market timing; Capital structure